FREQUENCY OF ANTIPHOSPHOLIPID SYNDROME IN DEEP VEIN THROMBOSIS: Frequency of Antiphospholipid Syndrome - Ahsan, Omar; Ahmed, Imran; Shabbir, Mohammad; Ahmed, Ijaz (Pakistan Armed Forces Medical Journal, 2008)
Objectives: To determine the frequency of antiphospholipid syndrome in patients of DVT.Study Design: Single center descriptive study.Place and Duration: It was carried out at Military Hospital Rawalpindi, from May to Oct 2003.Subjects and Methods: Fifty patients of either sex with Deep vein thrombosis (DVT) legs, who were diagnosed clinically and later on confirmed on doppler ultrasound, were selected through non-probability convenience sampling. doppler ultrasound was done to diagnose DVT and antiphospholipid antibodies tested namely lupus anticoagulant and anticardiolipin antibodies. Other associated risk factors were also documented. Data collected and organised, descriptive statistics were applied to calculate the frequencies. The results were organised in graphs and tables.Results: Out of 50 patients of DVT 38 (76%) were males and 12 (24%) were females. Mean age for males was 44.94±14.92 years whereas for females it was 27.66±5.97 years. Antiphospholipid syndrome was detected in 13(26%) patients; 11 (22%) were males and 2 (4%) females. Only lupus anticoagulant was detected in 9 (18%) patients. Anticardiolipin antibodies were detected in 3 (6%) patients. In 1 (2%) both lupus anticoagulant and anticardiolipin antibodies were detected.Conclusion: There is an association between antiphospholipid syndrome and DVT. Association of lupus anticoagulant is more, as compared to anticardiolipin antibodies with DVT. Additional risk factors make a person further susceptible to DVT.